La cesura: metro y sentido en el verso griego - Nieto Ibáñez, Jesús María (1992)
Because of the lack of agreement about how to define the caesura in Greek verse, this paper tries to emphasize on some aspects of crucial importance for the better understanding of the concrete carrying out of Greek caesura. On the one hand, the caesura is a main element in the metrical structure of verse; on the other, it is in close relation to its meaning and syntax. After exposing and commenting on examples proving this relation between metre and meaning, it will be insisted on the aspects of syntax and content as basic elements when considering the importance of the caesura in Greek Verse.
Keywords: Censura; Versificación; Poesía griega